EFEKTIVITAS METODE PENGAJARAN BAHASA ARAB - Ismail Baharudin (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2018)
Arabic is the language of the holy book Quran for mankind. Altough the Arabic language in Indonesia is a foreign language, but for muslim should not make foreign language in his tounge. Arabic for a Muslim is the fundamental key to unclock the deepening of knowledge of the religion of Islam. With a key that he can learn the basic teachings of religion and also be able to know the basic teaching of his religion, history, science, and culture of Islam that had reached the lighthouse internasional civilization before crushed by modern civilization today.Language teaching purposes, according to its name to grow and develop language skills. Skilled language means listening, skilled reading, and skilled writing in Arabic is good and right. Arabic language teaching methods have four forms taught to students. Teaching is in Arabic in this study is teaching Istima’ (listening), teacing Kalam (speaking), teaching Qiro’ah (reading), and teaching Kitabah (writing).